Incentive Pricing and Utility Regulation: A Comment - Jaffee, Bruce L. (Quarterly Journal of Economics, 1972)
Journal Article Incentive Pricing and Utility Regulation: A Comment Get access Bruce L. Jaffee Bruce L. Jaffee Indiana University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 86, Issue 1, February 1972, Pages 143–144, https://doi.org/10.2307/1880501 Published: 01 February 1972